Comparison of clinical efficacy of unilateral biportal endoscopic lumbar interbody fusion and osterior lumbar interbody fusion in the treatment of L4/5 lumbar disc herniation - Deng, Kuoang; Yang, Min; Xu, Yongtao (Frontiers in Surgery, 2025)
ObjectiveTo compare the clinical efficacy between unilateral biportal endoscopic lumbar interbody fusion (ULIF) and traditional posterior lumbar interbody fusion (PLIF) in the treatment of L4/5 lumbar disc herniation (LDH).MethodsA total of eighty-five patients with L4/5 LDH were enrolled and assigned into two groups: the ULIF group (n = 37) and the PLIF group (n = 48). Data regarding surgical conditions, hospital stay, perioperative Visual Analogue Scale (VAS) scores, Japanese Orthopaedic Association (JOA) scores, and serum inflammatory factor levels were recorded.ResultsNo statistically significant differences were observed in preoperative clinical characteristics (including age, disease duration, BMI, gender distribution, preoperative VAS scores, JOA scores, and serum inflammatory factor levels) between the two groups (all P > 0.05), indicating good comparability. Compared with the PLIF group, the ULIF group was associated with significantly less intraoperative blood loss, reduced postoperative drainage volume, and a shorter postoperative hospital stay (all P < 0.05). Additionally, the ULIF group exhibited lower serum levels of interleukin-6 (IL-6) and C-reactive protein (CRP) at 24 h postoperatively, as well as significantly lower VAS scores and higher JOA scores at 7 and 30 days postoperatively (all P < 0.05). However, the ULIF group was associated with a longer operative time and a higher number of intraoperative C-arm fluoroscopies compared with the PLIF group (both P < 0.05).ConclusionULIF exhibits significant advantages in minimally invasive. Although it requires longer operative time and more intraoperative fluoroscopies, it is associated with reduced blood loss, attenuated inflammatory responses, shorter hospital stay, and superior early postoperative pain and functional recovery, facilitating patient rehabilitation.